PERSEPSI MASYARAKAT TERHADAP KUALITAS PELAYANAN KESEHATAN (Studi Kasus Di Ruangan Kelimutu Kelas Iii Rumah Sakit Umum Daerah Prof. Dr. W. Z. Johannes Kupang) - Kaballu, Indah Dewi Yanti Lali; wadu, Jacob; Kolianan, Jim Briand; Pandi, David (Kybernology Jurnal Ilmu Pemerintahan dan Administrasi Publik, 2025)
Health is a fundamental human right that must be fulfilled by the state through the provision of quality health services. Prof. Dr. W. Z. Johannes Regional General Hospital in Kupang, as the main referral hospital in East Nusa Tenggara, has an important responsibility in delivering high-quality health services to the community. This study aims to analyze public perceptions of the quality of health services in the Kelimutu Ward Class III, using a descriptive qualitative approach. Data were obtained through observation, interviews, and documentation involving patients, patients’ families, and healthcare workers. The results indicate that public perceptions of services in this ward vary. Although most respondents consider the medical services to be fairly good, there are complaints regarding inadequate physical facilities, such as overcrowded and hot rooms, as well as delays in medication services. Based on the SERVQUAL theory proposed by Zeithaml, Parasuraman, and Berry, the most evident weaknesses are found in the dimensions of tangibles and responsiveness. These findings emphasize the importance of improving physical facilities and service responsiveness as efforts to enhance patient satisfaction and the hospital’s public image.